Fulminant isolated adenovirus hepatitis 5 months after haplo‐identical HSCT for AML. Issue 10 (26th August 2015) - Detrait, Marie; De Prophetis, Stephanie; Delville, Jean‐Pierre; Komuta, Mina
Key Clinical Message The principal limitation of allogeneic hematopoietic stem cell transplantation except relapse remains the transplant‐related mortality (TRM). In addition to graft‐versus‐host disease (GvHD), infections contribute to TRM in many patients. We describe herein a case of an adult patient presenting 5 months after haplo‐identical transplantation an isolated fulminant hepatitis due to adenovirus.